2000
DOI: 10.1021/jp994092u
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effect of N,N-Dialkylamides on the Intermolecular Hydrogen Bonding with Thioacetamide

Abstract: The alkyl substituent effect on the intermolecular hydrogen-bonding properties of tertiary amides has been investigated experimentally and theoretically. N, N-Dimethylformamide (DMF), N,N-diethylformamide (DEF), N,N-diisopropylformamide (DIF), N,N-dimethylacetamide (DMA), N,N-diethylacetamide (DEA), and N,Ndiisopropyl acetamide (DIA) were chosen as proton acceptors for thioacetamide (TA) in CCl 4 solution. Thermodynamic parameters for the interaction of tertiary amides with TA have been measured by nearinfrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 40 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…Also, the V E m values are more negative for ACN + DMA than those for ACN + DMF. This is due to the fact that electron density at oxygen atom of the carbonyl atom of DMA is greater than that of DMF [2,32] due to the presence of -CH 3 group at the carbon atom carbonyl group in DMA, resulting in stronger interactions in (ACN + DMA) system. Another contribution to negative V E m comes from the fitting of small ACN molecules (molar volume = 52.845 cm 3 AE mol À1 at T = 298.15 K) into the voids created by three-dimensional hydrogen bonded network of FA molecules [33] and into the voids present in bigger DMF/NMA/DMA molecules (molar volumes: DMF = 77.3767 cm 3 AE mol À1 , NMA = 76.5982 cm 3 AE mol À1 , DMA = 93.0272 cm 3 AE mol À1 at T = 298.15 K).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the V E m values are more negative for ACN + DMA than those for ACN + DMF. This is due to the fact that electron density at oxygen atom of the carbonyl atom of DMA is greater than that of DMF [2,32] due to the presence of -CH 3 group at the carbon atom carbonyl group in DMA, resulting in stronger interactions in (ACN + DMA) system. Another contribution to negative V E m comes from the fitting of small ACN molecules (molar volume = 52.845 cm 3 AE mol À1 at T = 298.15 K) into the voids created by three-dimensional hydrogen bonded network of FA molecules [33] and into the voids present in bigger DMF/NMA/DMA molecules (molar volumes: DMF = 77.3767 cm 3 AE mol À1 , NMA = 76.5982 cm 3 AE mol À1 , DMA = 93.0272 cm 3 AE mol À1 at T = 298.15 K).…”
Section: Discussionmentioning
confidence: 99%
“…Similar inference has also been drawn by Kim et al in their study on substituent effect of N,Ndialkylamides on intermolecular hydrogen bonding with thioacetamide in CCl 4 solvent using theoretical and experimental techniques. 85 Their studies showed that stability of the hydrogen-bonded complex between thioacetamide and amides had increased with increase in electron-donating alkyl group. The HB acceptor ability have often been linked to proton affinity of that site.…”
Section: Computationalmentioning
confidence: 99%
“…The electron density at oxygen atom of the carbonyl atom of DMAc is greater than that of DMF due to the presence of methyl group at carbon atom of carbonyl group in DMF resulting in stronger interaction in thesystem [39,40]. The values of ethyl benzoate + DMA are in between these two.…”
Section: Resultsmentioning
confidence: 97%